THE IMPLEMENTATION FAIR TRADE SYSTEM BASED ON THE NATURAL POTENCIAL RESOURCES IN EFFECTIVE AND EFFICIENT WAYS THROUGH THE ASEAN FREE TRADE ERA - S, Dian Nawastuty (Indonesian Journal of International Law, 2016)
Indonesian economic development’s dimension in free trade zone era will held upon to form the development pillars frameworks. The Indonesian development pillars which are : to pull the destitution out, to absorb the man power, and to develop the economic. However, the main problem to held the development pillars frameworks is the barrier in pulling the destitution out. Pulling the destitution out which are mean by the writers team in these article especially for the traditional farmer. These statement is counted also for the farmer whom works at the place with a lot of natural potential resources . These place with a lot of natural potential resources cannot give any of economic’s benefit. The incapacity of the place with a lot of natural potential resources to solve the people’s problem of needs caused the rate of destitution in Indonesia getting higher every year. In free trade zone of ASEAN’s frame work it is necessary to held some new brand penetration to support the new program by created fair trade system. These fair trade system should be based on the natural potential resources of Indonesia. To find the best solution to solve all of the matters above, the writers team using the normative judicial’s approach method in puposed to knowing and to describing the implementation of fair trade system based on natural potential resources effective and efficient ways trough the free trade zone era.